Leo Strauss and the crisis of rationalism : another reason, another enlightenment - Pelluchon, Corine; Howse, Robert, 1958- (Albany : State University of New York Press, 2014)
"Examines the German and Jewish sources of Strauss's thought and the extent to which his philosophy can shed light on the crisis of liberal democracy"--Provided by publisher.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Strauss, Leo; Philosophy and religion -- History -- 20th century; Philosophy, German -- History -- 20th century; Haskalah; PHILOSOPHY / Eastern; Electronic books